Climate impacts and adaptation strategies for coastal erosion, aquaculture, and tourism along the Adriatic side of Apulia region - Parete, Giuseppe; Bruno, Maria Francesca; Calabrese, Pietro; Carlucci, Roberto; Chiarulli, Miriam; D'Onghia, Gianfranco; Fiore, Annunziata; Fratino, Umberto; Longo, Caterina; Longo, Francesco; Scorrano, Serena; Gentile, Francesco (Frontiers in Climate, 2024)
This study addresses the imperative need for adaptation strategies to climate impacts in coastal areas, particularly vulnerable to climate change effects. Under the Interreg project "AdriaClim," our research aims to provide a comprehensive account of predicted climate impacts and corresponding adaptation measures for three key sectors for the coastal economy of the Puglia region (Southern Italy): coastal erosion, aquaculture, and tourism. Analyzing regional climate projections, predicted climatic anomalies for Apulia have been delineated. Together with a comprehensive description of the investigated sectors, the expected sectoral climate impacts have been identified. The respective adaptation measures for each sector have been evaluated in terms of coherence with the studied context and effectiveness, among those proposed in the literature. In aquaculture, climate change may influence ecosystem structure, functionality, production cycles, infrastructure, and organism physiology. Integrated multitrophic aquaculture (IMTA) emerges as a solution to enhance the resilience of Apulian aquatic production systems to climate change. For coastal tourism, the vulnerability to various climate impacts is emphasized. These impacts can directly influence tourist flows or indirectly alter the attractiveness of the Apulian Adriatic coast. Given the sector's strong ties to anthropic, natural, and cultural elements, a comprehensive adaptive approach proves most effective. Concerning coastal erosion, results underscore the prevalence of numerous stretches of eroding low coastline, with future projections indicating scenarios of widespread retreat along the southern Adriatic coast. Consequently, protective, and coastal management measures become imperative. The analyses and the obtained results 1 Parete et al.serves as a valuable knowledge framework essential for formulating a climate change adaptation plan for the Apulian Adriatic coast, aligning with the regional authorities' orientations.